2011
DOI: 10.1016/j.neuron.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

The Dendritic Branch Is the Preferred Integrative Unit for Protein Synthesis-Dependent LTP

Abstract: Summary The late-phase of long-term potentiation (L-LTP), the cellular correlate of long-term memory, induced at some synapses facilitates L-LTP expression at other synapses receiving stimulation too weak to induce L-LTP by itself. Using glutamate uncaging and two-photon imaging, we demonstrate that the efficacy of this facilitation decreases with increasing time between stimulations, increasing distance between stimulated spines and with the spines being on different dendritic branches. Paradoxically, stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
390
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(427 citation statements)
references
References 53 publications
34
390
1
2
Order By: Relevance
“…Remarkably, a local protein synthesis is assumed to be necessary for establishing late phase synaptic plasticity (14 -18). Considering that most of the changes may occur in a very limited space, as claimed by the cluster plasticity hypothesis (16,112), no dramatic increase of total protein level changes could be expected.…”
Section: Discussionmentioning
confidence: 97%
“…Remarkably, a local protein synthesis is assumed to be necessary for establishing late phase synaptic plasticity (14 -18). Considering that most of the changes may occur in a very limited space, as claimed by the cluster plasticity hypothesis (16,112), no dramatic increase of total protein level changes could be expected.…”
Section: Discussionmentioning
confidence: 97%
“…LTP maintenance is achieved by an interaction between input-specific 'synaptic tags', set by LTP induction, and the capture of PRPs synthesized in the soma or local dendritic domains. These are independent processes and can occur separately in time (Fonseca et al, 2004;Govindarajan et al, 2011;Redondo et al, 2010). Thus, according to the synaptic tagging and capture hypothesis, the maintenance of synaptic plasticity is a function of neuronal network activity and not only of the input stimulated at a given time.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Changes in spine morphology after chemical LTP (Refs. 12 and 22) and glutamate uncaging 26 could be observed, and it could be shown that spine neck plasticity regulates compartmentalization of synapses.…”
Section: Introductionmentioning
confidence: 95%